Desarrollo de un prototipo para la medición de caudal de agua empleando un sistema IOT-RF. - Chunga Malán, Jorge David (2023)
This project shows the design and construction of a prototype for measuring water flow using an IoT-RF system, with the purpose of obtaining exact water flow information through wireless networks, because, in several Water Boards Drinking sector, a designated person collects and records the water consumption of each user, noting this value on a record sheet. This type of records can give rise to various errors due to human error; it is possible that staff make mistakes when recording, reading or losing notes. This prototype allows us to obtain information on the water consumption of each user located at distant distances and store the entire consumption history, hosting the data on the Telegram platform, which backs up the information in the event of data loss. The water measurement plate has a flow sensor that allows the water flow to be measured, with the help of this Hall effect sensor, which in turn emits electrical pulses that can be read digitally. The conversion of electronic pulses is carried out by an ATMega328P microcontroller and then transfers the information to the Wifi LoRa 32 development board, which uses radio frequency (RF) to send the data to another LoRa module, which carries out the same process. The data obtained by the prototype is saved in the ATMega328P microchip in addition to the Telegram chat, with the time and date on which the query is made. The results of functional tests establish the reliability and efficiency of the prototype. Different parts of the system were evaluated, such as: data reading, transmission – reception, tests to determine data reading and reception errors in Telegram, these tests allow indicating the effectiveness of the prototype. In this way, the prototype complies with the IoT-RF system that was proposed as a starting point.